The Comparison of Entrepreneurial Firms for the Use of Financial Management - Knapová, Bohuslava (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
It is evident from the article how important is to paying attention to all mentioned methods of the comparative analysis, which can be the suitable instrument for the first-rate financial management of selected entrepreneurial firms. The article has been written as an output of a research plan Development of Financial and Accounting Theory and Its Application in Practice from Interdisciplinary Point of View.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 195-199